P01 Heartflow: experience of a high-volume district general hospital. (7th September 2020) - Qayyum, Shahzad; Habib, Abubakar; Kechyn, Svyatoslav; Auger, Dominique; Damani, Nizar; Griguer, Anne; Hadjiloizou, Nearchos; Jain, Piyush; Keenan, Niall; Khan, Masood; Prabhakar, Anisha; Rosenfeld, Kevin; et al.
Abstract : Introduction: HeartFlow is a non-invasive technique for estimating fractional flow reserve (FFRCT ) from computer tomography coronary angiography (CTCA). HeartFlow has been made available via an NHS England funded program since September 2018 and is now fully embedded within our stable chest pain pathway. The aim of this work was to evaluate the impact of HeartFlow, which replaced previous practice of stress testing for patients with moderate coronary lesions, and invasive angiography for those with severe stenoses on CTCA. Methods: We reviewed 360 consecutive patients who underwent CTCA and FFRCT between September 2018 and June 2019. CT coronary angiograms and HeartFlow models were read by a cardiologist and radiologist. Clinical records of all patients were reviewed. Results: All patients referred for FFRCT had coronary stenoses greater than 50%. 72% had FFRCT ≥0.8 and were discharged. 26% had FFRCT <0.80 and underwent invasive coronary angiography. 1% were unsuitable. Of the patients referred for invasive angiography, 39% underwent PCI, 14% were referred for bypass surgery, 5% had chronic total occlusions and 4% had no suitable targets for revascularization. 34% of patients with FFRCT <0.80 had discordant findings on invasive pressure wire assessment, and revascularization was deferred. Conclusion: Our study demonstrates the impact of HeartFlow in a high-volume CTCA service. Two thirds of patients referred for HeartFlow, who would previously have undergone downstream testing, had negative results and the pathway stopped at that point. Of the patients referred for invasive assessment, significant disease was found in two thirds, and in one third significant stenoses were not identified.